Benefits of Conventional Chemotherapy in Progressive Disease Patients with Tyrosine-Kinase Inhibitors: A Case Report - Ahmad Junaidi; Sabrina Ermayanti; Afriani Afriani (HM Publisher, 2022)
Background. Mutation of the epidermal growth factor receptor (EGFR) in non-small cell lung carcinoma is a favorable predictive factor for targeted EGFR tyrosine kinase inhibitor (TKI) therapy, but patients with EGFR-mutated lung cancer who are given EGFR-TKI will experience disease progression after average 10 to 14 months on average. This study aims to describe a case of progressive lung adenocarcinoma and its chemotherapy treatment. Case presentation: A 54 years old woman who came with stage IV left lung adenocarcinoma (exon 21 mutation) who had received EGFR TKI for 17 months progressed, so the treatment was shifted to systemic chemotherapy. Based on these diagnostic results, the patient was diagnosed with progressive disease T3N1M1c left lung adenocarcinoma (pleura, contralateral nodule, ribs, suprarenal) Stage IVb PS ECOG 0. The patient was then treated with conventional doublet-platinum-based chemotherapy with the Carboplatin-Paclitaxel combination. Conclusion: Systemic chemotherapy with doublet-platinum is an option in patients with progressive adenocarcinoma with EGFR-TKI who cannot obtain tissue for histopathological examination at rebiopsy or do not have access to advanced molecular biology (e.g., T790M) or follow-up therapy (third-generation TKI, osimertinib).